Güç elektroniği sistemlerinde yarı iletken anahtarlama elemanlarının statik ve dinamik karakteristiklerinin deneysel olarak belirlenmesi - Yavuz, Erdal (My University, 2002)
Power electronics is that field of electronics which deals with conversion, control and switching of electrical anergy for power applications and playing a major role in revolutionizing the industrial processes. It provides the essential link between micro level of electronic controllers and the mega watt level of industrial power and process requirements. There are power electronics applications within the entire fields of electrical energy systems. Problems, such as d.c. to d.c. conversion and regenarative braking etc., which were earlier completely unrealistic have now been solved by means of power electronics. Power electronics thus acts as an interface between the electrical power source and the consumer's load and occupy indispensable position in every walk of life. Certainly, the main target of technical education is to educate qualified people equipped with contemporary knowledge. There has been continuous improvement in power electronics several new devices are being continuously invented. Power electronics is therefore, justifiably taught in almost all the technical institutions and used by the process industry. In this study, power electronics systems are considered with current data. Numerical experiment values have been determined by the measurements made in the Power Electronics Laboratory of Electrics Department of Technical Education Faculty at Marmara University. Characteristics curves have been recorded and evaluated with a digital oscilloscope.
Keywords: Elektrik